New genera and species of Neotropical Rhinotragini (Coleoptera, Cerambycidae, Cerambycinae) - Santos-Silva, Antonio; Bezark, Larry G.; Martins, Ubirajara R. (Zootaxa, 2012)
Giesberteclipta and Thomasella, two new genera of Rhinotragini Thomson, 1861 (Coleoptera: Cerambycidae: Cerambycinae), are described and illustrated. Six new species are also described and illustrated: Acyphoderes violaceus from Costa Rica; Ischasioides giesberti from Ecuador, and Oxylymma pallida, Pseudagaone williamsi, Stultutragus tippmanni and S. ventriguttatus from Brazil. Keys are provided for the known species of Pseudagaone Tippmann, 1960, Giesberteclipta, and Oxylymma Pascoe, 1859 and for parts of Ischasioides Tavakilian & Peñaherrera-Leiva, 2003 and Stultutragus Clarke, 2010.  The following new combinations are proposed: Giesberteclipta costipennis (Giesbert, 1991); G. monteverdensis (Giesbert, 1991); Thomasella igniventris (Giesbert, 1991), and Stultutragus romani (Aurivillius, 1919). The following three new country records are reported: Oxylymma durantoni Peñaherrera-Leiva & Tavakilian, 2003 (Brazil), Oxylymma sudrei Peñaherrera-Leiva & Tavakilian, 2003 (Brazil), and Ommata (Eclipta) faurei Peñaherrera-Leiva & Tavakilian, 2003, all from Brazil.